The effects of UV exclusion on the soluble phenolics of young Scots pine seedlings in the subarctic - Turunen, Minna; Heller, W.; Stich, S.; Sandermann, H.; Sutinen, M.-L.; Norokorpi, Y. (Environmental Pollution, 1999)
The characteristics of UV-absorbing compounds, particularly soluble phenolics were studied in needles of a 63-day-old seed-grown Scots pine (Pinus sylvestris L.) seedlings of two provenances in a UV exclusion field experiment at Pallas-Ounastunturi National Park in Finnish Lapland (68°N, 270 m a.s.l.). The experiment used the following plastic filters in exclosure treatments to manipulate the spectral balance of natural irradiance: (1) 'control' (a polyethene plastic filter); (2) 'UV-B exclusion' (a clear polyester filter); and (3) 'UV-B/UV-A exclusion' (a clear acryl plate). Polyethene transmitted 89% of the ambient levels of total UV (280-400 nm), polyester transmitted 75% of the total UV, but only 0.6% of the UV-B (280-315 nm) component, while acryl plate transmitted 0.2% of UV, (280-360 nm). The research also included (4) 'Ambient' plants that were not subjected to any treatment exclosures. After the 58 day UV exclusion, significant (p < 0.0001) differences due to treatments were determined for a kaempferol derivative, kaempferol 3-glucoside, and a quercetin derivative, the quantities of which ranged from 0.23 to 0.45, 0.42 to 1.34 and 0.39 to 0.75 μmol g FW-1, respectively, depending on treatment and provenance. Overall, Scots pine seedlings grown at ambient UV radiation (PAS300, Caldwell's generalized Plant Action Spectrum (PAS) normalized at 300 nm, 72 mW m-2 or under a control had a significantly (p < 0.05) higher quantities of soluble phenolics than seedlings grown under UV-B or UV-B/UV-A exclusion treatments. There were no significant differences in the quantity of soluble phenolics between the two exclosure treatments or between the two Scots pine provenances. The sums of diacylated flavonol glucosides ranging from 3.75 to 4.55 μmol g FW-1 depending on treatment and provenance, were already present at very low UV-levels under the UV-B/UV-A exclusion treatment. The present study indicated that soluble phenolics, particularly the diacylated flavonol glucosides, may provide an effective preformed ...